SGOT/SGPT levels in blood serum on rats (Rattus norvegicus) that CCl4 induced then its treatment by ethanol extract of Curcuma xanthorrhiza rhizome as hepatoprotector - Hamida Nurlaila; Aulanni’am AULANNI’AM; Fahmi Dimas Abdul Azis; Sasangka PRASETYAWAN (UNIB PRESS, 2022)
CCl4 is a xenobiotic compound that could be entered into body by digestion and ingestion system. It trigger to produce ROS until lipid peroxydation which can increase SGOT/SGPT levels on blood serum. Both SGOT and SGPT are transaminase enzymes that activated on blood serum and they were produced in hepatocyte. If there are radicals in hepatocyte as final product of lipid peroxydation, then they are exit from cytoplasm on hepatocyte to intravenous so theirs levels is increase in blood. Producing of radicals from ROS in lipid peroxydation can be scavenged by antioxidant compounds on ethanol extract of Curcuma xanthorrhiza rhizome. This research are aimed to determine of SGOT/SGPT levels on blood serum in each of groups. This research used male rats that divided into five groups, that were negative control (A group), positive control (CCl4 10% induced (B group)) and therapy groups (200, 400, and 800 mg/kg BW of Curcuma xanthorrhiza rhizome ethanol extracts (C, D, E groups respectively)). SGOT/SGPT levels was analyzed, its result was 165/92, 264/141, 161/64, 130/59 and 135/55 U/L respectively. Based on the Tukey’s HSD test (p = 0.1), SGOT/SGPT levels in positive control was significance different (p < 0.1) to negative control, but theirs levels in 400 and 800 mg/kg BW of Curcuma xanthorrhiza rhizome ethanol extract therapy groups were not significance different (p > 0.1) to negative control. Thereby, 400 and 800 mg/kg BW of Curcuma xanthorrhiza rhizome ethanol extracts was more effective as hepatoprotector which known from decreasing of SGOT/SGPT levels.